Maternal and Child Health in South Sudan: Priorities for the Post-2015 Agenda. (17th April 2015) - Mugo, Ngatho; Zwi, Anthony B.; Botfield, Jessica R.; Steiner, Caitlyn
The Republic of South Sudan continues to face considerable challenges in meeting maternal, newborn and child health (MNCH) care needs and improving health outcomes. Ongoing instability and population displacement undermine scope for development, and damaged infrastructure, low coverage of health services, and limited government capacity and a human resource base have resulted in a fragmented health system. Despite considerable attention, effort and support, the issues and challenges facing South Sudan remain deep and sustained, and urban–rural disparities are considerable. There is a need to maintain investments in MNCH care and to support developing systems, institutions, and programs. This review of the literature offers a commentary and appraisal of the current MNCH situation in South Sudan. It explores the barriers and challenges of promoting MNCH gains, and identifies priorities that will contribute to addressing the Millennium Development Goals and the emerging health priorities for the post-2015 development agenda.